ANALISIS REAKSI PASAR TERHADAP PENGUMUMAN RIGHT ISSUE (STUDI KASUS PADA SAHAM YANG TERDAFTAR DI ISSI) - Moch. Ali Fudin Al Islami; Imron Mawardi (Universitas Airlangga, 2019)
This research aims to find out and explain market reactioncaused by existing action corporate advertisement which is the right issue done by the issuer who was listed in Indonesia Sharia Stock Index period 2014-2016.There are 20 issuers who become the research sample with the period of observation is 29 days. The approach used in this research is quantitative approach by using event study method which is the approach that is specialized to analyze a particular event that is believed to have an impact or reaction. The focus of the research is to see the reaction shown by the change of Average Abnormal Return and Trading Volume Activity using one sample t-test and paired sample t-test. Data processing used a statistical tool of Stata version 14 by determining level of significance of 5%.The results of the research show that there is a significant average abnormal return before and after the right issue and there is a significant difference in trading volume activity before and after the right issue.Keywords: Sharia Stock, Right Issue, Abnormal Return, Trading Volume ActivityREFFERENCESBeaver, William H. 1968. The Information Content of Annual Earning Releases : A Trading Volume Approach. Supplement to journal of Accounting ResearchBrigham, Eugene dan Joel F Houston, 2001. Manajemen Keuangan II. Jakarta:Salemba EmpatHermuningsih, Sri., Wardani D, K. (2009). Analisis Reaksi Pasar Modal Terhadap Peristiwa Right Issue Dan Pengumuman Deviden Yang Ditunjukkan Oleh Abnormal Return.Yogyakarta. Fakultas Ekonomi Universitas Sarjanawiyata Tamansiswa. ISSN:2086-0390.Husnan, Suad. (1994). Dasar-Dasar Teori Portofolio dan Analisis Sekuritas. Edisi I. Yogyakarta: Penerbit UPP AMP YKPNHusnan, Suad. (1996). Dasar-dasar teori portofolio dan analisis sekuritas. Edisi II. Yogyakarta: UPP AMP YKPNHusnan, Suad. (2005). Dasar-dasar teori portofolio dan analisis sekuritas.Edisi v. Yogyakarta: UPP AMP YKPNIndonesian Stock Exchange. 2017. Indonesian Capital Market Directory 2017. Jasmine, Aldila., (2015). Reaksi Pasar Terhadap Stock Split Pada Emiten Saham Syariah Yang Terdaftar Di Bursa Efek Indonesia Periode 2011-2014. Surabaya. Fakultas Ekonomi dan Bisnis Universitas Airlangga.Jogiyanto, H. M. (2003). Teori Portofolio dan Analisis Investasi. Edisi Ketiga. Yogyakarta: BPFE Universitas Gajah Mada.Jogiyanto, H. M. (2009). Teori Portofolio dan Analisis Investasi. Edisi Keenam. Yogyakarta: BPFE Universitas Gajah Mada.Latan, Hengky. (2014). Aplikasi Analisis Data Statistik Untuk Ilmu Sosial Sains Dengan Stata. Bandung. Alfabeta.Maguire, Frances. “The Banker”. 2007.Rusdi, Dedi dan Avianto, Angga.(2009). Pengaruh Right Issue Terhadap Tingkat Keuntungan Dan Likuiditas Saham Emiten Di Bursa Efek Jakarta. Fakultas Ekonomi Universitas Islam Sultan AgungSamsul, Mohammad. 2006. Pasar Modal dan Manajemen Portofolio. Jakarta: ErlanggaSugiyono. 2012. Metode Kuantitatif, Kualitatif dan R&D. Cetakan ke-17. Bandung: Alfa BetaUtomo,V.J. 2015. ”Efek Hari Libur Lebaran Pada Emiten yang Terdaftar dalam ISSI Periode 2011-2013” Surabaya.Fakultas Ekonomi dan Bisnis Universitas Airlangga.(www.ksei.co.id/services/corporate_action_services, diakses tanggal 10 Oktober 2017) ______________IDX Fact Book 2016.Bursa Efek Indonesia. Jakarta______________IDX Annualy Statistics 2014.Bursa Efek Indonesia. Jakarta______________IDX Annualy Statistics 2015.Bursa Efek Indonesia. Jakarta______________IDX Annualy Statistics 2016.Bursa Efek Indonesia. Jakarta______________Undang-Undang No. 8 Tahun 1995 Tentang Pasar Modal